THE NEED FOR ARABIC LANGUAGE TEACHING MATERIALS BASED ON MULTICULTURAL EDUCATION FOR INDONESIAN DIASPORA STUDENTS - Nuruddin; Budiaman; Andri Ilham (ALSINATUNA, 2021)
This study aims to analyze the need to develop Arabic teaching materials models that contain multicultural-based character education values, especially in Indonesian foreign school (Sekolah Indonesia Luar Negeri), Jeddah, Riyadh, and Makkah. This research is the first step of the research and development model, which is to identify the needs of students, Arabic teachers, and school principals for Arabic teaching materials that contain multicultural values. The aim is to make learning Arabic at Indonesian foreign schools easier, more effective, fun, and produce Indonesian diaspora students who have a spirit of nationalism and respect plurality. Fun, and make Indonesian diaspora students confident in nationalism and respect plurality.  This study indicates that Arabic teaching materials in Indonesian schools abroad, especially in Arab countries, really need to be developed. The forms of development of teaching materials are manifested in three aspects, namely (1) related to Arabic language teaching materials based on the values ​​of national character education, by learning objectives, contextual with the times; (2) aspects of application technology, namely by developing Arabic teaching materials equipped with multimedia learning media such as audio, video, animation and others to make it easier to learn; (3) aspects of character education, namely Arabic teaching materials that contain character education values, such as religious values, nationalism, honesty, independence, cooperation, integrity, hard work and responsibility.